Synthesis of Eicosanyl (E)-Caffeate, a Metabolite of Calystegia Soldanella† - Venkateswarlu, Somepalli; S. Ramach, Marellapudi; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2010)
Eicosanyl (E)-caffeate (1), isolated from the stems of Calystegia soldanella has been synthesized starting from 3,4- dihydroxybenzaldehyde (2) in four steps with an overall yield of 29%.